2014
DOI: 10.1097/md.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Hepatitis B Core Antigen Levels in the Natural History of Chronic Hepatitis B

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 25 publications
1
55
1
Order By: Relevance
“…Quantitative detection of HBsAg (qHBsAg) and anti‐hepatitis B virus core antibody (anti‐HBc) was performed using available enzyme immunoassays (Roche Diagnostics, Penzberg, Germany) and sandwich enzyme‐linked immunosorbent assays, respectively . Serum HBV DNA was measured by COBAS AmpliPrep/COBAS TaqMan, with a minimum value of detection of 20 IU/mL . The levels of qHBsAg, anti‐HBc and HBV DNA were expressed as log 10 IU/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative detection of HBsAg (qHBsAg) and anti‐hepatitis B virus core antibody (anti‐HBc) was performed using available enzyme immunoassays (Roche Diagnostics, Penzberg, Germany) and sandwich enzyme‐linked immunosorbent assays, respectively . Serum HBV DNA was measured by COBAS AmpliPrep/COBAS TaqMan, with a minimum value of detection of 20 IU/mL . The levels of qHBsAg, anti‐HBc and HBV DNA were expressed as log 10 IU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…11 Serum HBV DNA was measured by COBAS AmpliPrep/ COBAS TaqMan, with a minimum value of detection of 20 IU/mL. 10 The levels of qHBsAg, anti-HBc and HBV DNA were expressed as log 10 IU/mL.…”
Section: Hepatitis (Hepatitis C Virus Infection [Hcv] Hepatitis D Vimentioning
confidence: 99%
“…These antibodies are known as the marker of a prior HBV infection or exposition, and they can persist 10-20 years or more after viral clearance. The level of these antibodies is known to fluctuate depending on the stage of HBV infection [27]. It has been shown that the levels were higher in cases of chronic HBV hepatitis than in OBI, and higher in OBI than in cases of past/cured HBV infection [28].…”
Section: Definitions Of Isolated Anti-hbc Pattern and Occult Hepatitimentioning
confidence: 99%
“…No cutoff value can confidently predict the disease activity due to significant overlap of HBsAg levels among patients with active and inactive diseases [14]. Furthermore, there is little information about hepatitis B core antibody (HBcAb) levels in the natural history of CHB [15,16]. And no data are available on hepatitis B e antigen (HBeAg) for differentiation of the natural phases of HBV infection.…”
Section: Introductionmentioning
confidence: 99%